Teoria e prática da guerra no reinado de Fernando III (1217-1252) - Moretti Junior, Augusto João (2015)
This dissertation analyzes war in the reign of Ferdinand III of Castile and Leon (1217-1252), emphasizing the theoretical and practical aspects governing that monarch's action in the procedure of his territorial conquest and centralization of royal power. We have divided this investigation into three research themes. At first, we discuss the concepts of just war and holy war. We make use of documentary sources such as the Jerusalem Bible (1995), The City of God (2000) of St. Augustine, the Etymologies (2004) of Isidore of Seville, the booklet In praise of the new knighthood (2005) of Bernard of Clairvaux, and the Summa Theologica (1990) of St. Thomas Aquinas. Secondly, we address the monarchical policy organized by Ferdinand III for the war and territorial expansion in Spain. Thirdly, we study the military strategies and tactics used in the fighting against the Muslims. These last two themes are based on the analysis of three main sources, namely the Crónica Latina de los Reyes de Castilla (1999), Crónica de Veinte Reyes (1991), and the Primera Crónica General de España (1955).